Meningkatkan Partisifasi Aktif Anak-Anak terhadap Karakter Religius dalam Kegiatan Keagamaan di Lingkungan Masjid Kampung Sambidingko Kelurahan Cikerai Cilegon - Surachman Surachman; Sanae Sanae; Suminah Suminah; Samsiyah Samsiyah; Hernawati Hernawati; Tatu Humrotul (Jurnal Kemitraan Masyarakat, 2024)
Character can be formed and developed which is a person's characteristic from human behavior. Character can also be influenced by various things such as the human family's own experiences, the surrounding environment, religion, and a person's personality. The aim of Community Service (PKM) in the religious sector by the KKM group 40 of Cikerai Village is to increase children's participation in the formation of religious character through positive activities, namely religious activities. This needs to be done considering technological developments and the digitalization era that is currently trending in society. This PKM method uses a PKM approach based on community participation actions. The PKM results show that religious activities in the Cikerai Subdistrict area are quite strong in the community considering that there are still religious figures and community leaders who still adhere closely to religious and cultural principles. So there was collaborative participation from both children and religious leaders around the Sambidingko Village mosque as well as KKM students who took the initiative to hold this religious activity.